Composting of municipal solid waste and farm wastes for its use as amendment in sodic soil - SINGH, Y. P.; ARORA, SANJAY; MISHRA, V. K.; DIXIT, H.; GUPTA, RAVINDRA K. (Journal of Soil and Water Conservation, 2017)
A study was conducted to utilize municipal solid waste and farm wastes in different combinations for composting with and without use of earthworms and lingo-celluloytic microbes. A total of seven combination treatments were set up for on-farm composting. The compost generated at maturity from different treatments was analyzed for physico-chemical properties and nutrient content to promote its use as soil amendment to improve fertility and productivity of sodic soil. The composting process was completed in all treatment at 120 days. During composting, temperature under different treatments varied between 24 to 27 oC and moisture content ranged between 43.88 to 69.32%. At maturity, the pH and EC of the matured compost increased slightly from 6.97 to 7.48 as compared to initial values of composting material. Total nitrogen, total phosphorus, total potassium and calcium contents also increased at the maturity of the compost. The prepared compost applied to sodic soil under rice-wheat cropping system indicated its ameliorative potential. The soil pH reduced from 9.8 to 8.8 and ESP reduced from 78.3 to 28.0 and there was build up organic C and nutrients. Bulk density and infiltration characteristics of soil also improved.